Leisure and Tourism Landscape / By JTart Publishing & Media. - JTart Publishing & Media (China : JTart Publishing & Media, 2013)
The book separately from the tourist resort parks. city parks. ecological parks. cultural parks. community parks . CBD and other aspects of comprehensive introduction to the park and leisure landscape fascinating place . Weave in content were the key points from the landscape scenarios .
engineering bookfair2015
Keywords: Landscape architecture; City planning